In vivo antimicrobial activity of marbofloxacin against Pasteurella multocida in a tissue cage model in calves - Cao, Changfu; Qu, Ying; Sun, Meizhen; Qiu, Zhenzhen; Huang, Xianhui; Huai, Binbin; Lu, Yan; Zeng, Zhenling (Frontiers in Microbiology, 2015)
Marbofloxacin is a fluoroquinolone specially developed for use in veterinary medicine with broad-spectrum antibacterial activity. The objective of our study was to re-evaluate in vivo antimicrobial activity of marbofloxacin against Pasteurella multocida using subcutaneously implanted tissue cages in calves. Calves were infected by direct injection into tissue cages with Pasteurella multocida(type B, serotype 2), then intramuscularly received a range of marbofloxacin doses 24h after inoculation. The ratio of 24h area under the concentration-time curve divided by the minimum inhibitory concentration or the mutant prevention concentration (AUC24h/MIC or AUC24h/MPC) was the pharmacokinetic-pharmacodynamic (PK/PD) index that best described the effectiveness of marbofloxacin against Pasteurella multocida (R2=0.8514) by nonlinear regression analysis. Marbofloxacin exhibited a good antimicrobial activity in vivo. The levels of AUC24h/MIC and AUC24h/MPC that produced 50% (1.5log10CFU/mL reduction) and 90% (3log10CFU/mL reduction) of maximum response were 18.60h and 50.65h, 4.67h and 12.89h by using sigmoid Emax model WINNONLIN software, respectively. The in vivo PK/PD integrated methods by tissue cage model display the advantage of the evaluation of antimicrobial activity and the optimization of the dosage regimen for antibiotics in the presence of the host defenses, especially in target animal of veterinary interest.